The portfolio in the teaching practice in primary education degree - Ana Mª Rico Martín (Revista Electrónica Interuniversitaria de Formación del Profesorado)
This paper takes as a starting point the description and study of the main characteristics of the portfolio as a tool for learning and formative assessment, to expose the relevance of this technique in the Teaching Practice module in the degree in Primary Education. As an argument for the use of portfolio a proposal for the development, implementation and assessment of it is presented. This proposal will be taken by future teachers during their teaching practice period in Primary education classroom.